ECOLINGUISTICS: LANGUAGE SELECTION POLICIES IN THE SCOPE OF FAMILY AND SOCIETY IN PUBLIC SPACE - abdul haliq (Balai Bahasa Sulawesi Tengah, 2018)
This study aimed to find out two things, namely (1) the factors that influence the family determine language selection policy; (2) factors that influence society in the use of language in public spaces. This study took samples in several regions including, Magelang, Wonogiri, Yogyakarta, Makassar, and Tanjung Pinang. The type of research used is qualitative. Data collection techniques are carried out by observation and interviews. The collected data is then analyzed using descriptive qualitative techniques. Based on the results of the study, it can be concluded that (1) the choice of language used in the family sphere is influenced by factors, namely the first language of family members, the language used in the neighborhood, the language of education and the media; (2) the language used in public space is basically regulated by the government, however, the use of language still tends to hit rules, especially the language used for advertising.